Memasyaratkan Sholawat Nariyah Di Bumi Nusantara - Holidi, Ahmad Farhan; Surur, Miftahus (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2019)
The tradition of reading the Nariyah prayer individually and in congregation has taken root in the midst of the community especially in Situbondo district, in every corner of the city and remote villages even though every day is not empty from reciting the 4444 shalawat nariyah individually and in congregation, so that Situbondo district is the term